PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA DALAM PERSPEKTIF KOMUNIKASI PEMBANGUNAN DI SURAKARTA - Muhammad Fajar Pramono; Syamsulhadi Syamsulhadi; Mudiyono Mudiyono; Sunarru Samsi Hariadi (Universitas Muhammadiyah Sidoarjo, 2013)
Street traders (PKL) has long been a serious concern central and local governments, including the city of Surakarta. The problem is not the policy level, but associated with its implementation. The expected goals of this study was to determine the depth and the coaching setup process hawkers (PKL) conducted by Government of Surakarta, especially during the leadership of Mayor Joko Widodo, can be done peacefully and to investigate fundamental differences and fostering arrangement patterns PKL with the previous leadership in Surakarta in the perspective of development communication.This research using qualitative and quantitative approach. The results showed that the effectiveness of the arrangement and development of street vendors in Surakarta, so that it can be done peacefully greatly influenced by factors communicator, message, medium, communicant and effect (Lasswell, 1948). However, among these factors is the most dominant factor communicator (leadership) and medium (interpersonal communication). Leadership style using patterns Jokowi more situational leadership. While the implementation of interpersonal communication is nguwong-ke.